PREVENTION AND INTERVENTION OF STUNTING IN INDONESIA: A SCOPING REVIEW - Nadirawati, Nadirawati; Suryaningsih, Chatarina; Virgona Bangun, Argi; D. Dela Rosa, Ronnell (jfpublisher, 2023)
Introduction. Stunting manifests chronic nutritional deficiency that can begin in the baby in the womb and after birth. This study identifies and describes various stunting prevention and management efforts reported in the literature in Indonesia. This study was to obtain an overview of the prevention and efforts to treat stunting; it is hoped that it will produce the best efficacy information and can be scientifically accounted for so that it can be applied as a national policy in Indonesia. Methods. We reviewed Indonesian and English articles published between 2018 and 2022 through ProQuest, PubMed, and Google Scholar search data engines. The search generated 2,454 articles. All selected studies were systematically evaluated and screened based on title, open access, and full text related to the research objectives. Finally, 10 articles were included in the learning. Stunting prevention and intervention efforts are identified from the selected articles and presented in the extraction table. The final conclusion is made based on the types of intervention from the articles obtained. Results. The results showed that there were 2 types of interventions to overcome stunting in toddlers, namely preventive and curative. Preventive intervention is carried out by conducting health education, mentoring and counselling for families, mothers, and caregivers of stunting toddlers, while curative interventions are provided by improving food intake and adding nutrients. Conclusion. This study describes a variety of stunting prevention and interventions that have been reported in the literature. Further research on the management of stunting with comorbidities is needed because stunting children are a population at risk for complications.